2019
DOI: 10.1177/0961203318821176
|View full text |Cite
|
Sign up to set email alerts
|

Utility of neutrophil-to-lymphocyte ratio plus C-reactive protein for infection in systemic lupus erythematosus

Abstract: Distinction between infection and flare in patients with systemic lupus erythematosus (SLE) is a challenge in clinical practice. Objective To analyze the utility of neutrophil-to-lymphocyte ratio (NLR) plus C-reactive protein (CRP) to differentiate between infection and active disease in patients with SLE. Methods A cross-sectional study of a cohort of patients with SLE was carried out. Blood samples from four groups (patients without infection or active disease, patients with infection, patients with active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 25 publications
4
41
1
Order By: Relevance
“…These 185 episodes were divided into 4 groups: infected-active episodes as group A (n = 102; 55%), infected-inactive episodes as group B (n = 11; 6%), noninfected-active episodes as group C (n = 59; 32%), and noninfected-inactive episodes as group D (n = 13; 7%) ( Table 2). In the similar studies of adult SLE patients comparing parameters from the four groups, the trend of our CRP results is the same as three reported literatures [18,28,32]. While the trend of ESR and PCT are also in consistent with those of Schäfer et al and Wang et al, respectively (supplement Fig.…”
Section: Patient and Clinical Characteristicssupporting
confidence: 91%
See 3 more Smart Citations
“…These 185 episodes were divided into 4 groups: infected-active episodes as group A (n = 102; 55%), infected-inactive episodes as group B (n = 11; 6%), noninfected-active episodes as group C (n = 59; 32%), and noninfected-inactive episodes as group D (n = 13; 7%) ( Table 2). In the similar studies of adult SLE patients comparing parameters from the four groups, the trend of our CRP results is the same as three reported literatures [18,28,32]. While the trend of ESR and PCT are also in consistent with those of Schäfer et al and Wang et al, respectively (supplement Fig.…”
Section: Patient and Clinical Characteristicssupporting
confidence: 91%
“…1). Like the result from Broca-Garcia et al, infected-active group (group A) had the highest values of PLR among all four groups [28].…”
Section: Patient and Clinical Characteristicssupporting
confidence: 70%
See 2 more Smart Citations
“…NLR is closely associated with most common inflammatory biomarkers, such as C-reactive protein and erythrocyte sedimentation rate (44)(45)(46)(47)(48)(49). A growing body of evidence suggests that NLR may act as excellent indicator of inflammation status in various diseases, such as Crohn's disease (49), cancer (50,51), infection (52,53), and rheumatic diseases (54)(55)(56). Moreover, numerous studies also reported that NLR was closely related to inflammatory response and SLE disease activity (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: ' Discussionmentioning
confidence: 99%